Campus Canopy, 1949-04-16 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1949)
Concert Presented Here Apr. 23 by Tech Glee Club -- Classes Elect President for Coming Year -- Dixie Dewers Win Amateur Prize For English Club -- Dr. Durrenberger Is Chosen Dean -- Miss Ivey Announces Plans For May Day
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals